Characterization of Genome Sequence 2019 Novel Coronavirus (2019-nCoV) by using BioinformaticTool. Issue 1 (May 2020) - Parmin, N. A.; Hashim, Uda; Hamidah A Halim, N.; Uda, M.N.A; Afnan Uda, M.N.
Abstract: A novel coronavirus (2019-nCoV) became the seventh member in the family of Coronavirus that infect human. 2019-nCoV became the most severe virus compare to another family of coronavirus. Human airway ephitelial cells have been used to identify and isolate the virus before proceed to reverse trancriptase Polymerase Chain Reaction (RT-PCR). Detailed biological knowledge is crucial for the development of effective countermeasures, diagnostic tests, vaccines and antiviral drugs against the 2019-nCoV. Conserved coding sequences within the spike glycoprotein region of open reading frame in the coronavirus genome was used as the basis to design oligonucleotide probe to detect the virus. Analyses on different strain of coronavirus sequences were done to check the percentage of similarity and consensus region that cause different strain of viruses. The biomarker needed an acceptable length between 22 and 31 mers. The choice of S gene region was identified and can be used as a biomarker probe for biosensor development. It has implications for coronavirus detection techniques in clinical and biosensor diagnostic system.